2015
DOI: 10.1002/tox.22086
|View full text |Cite
|
Sign up to set email alerts
|

Deep sea minerals prolong life span of streptozotocin‐induced diabetic rats by compensatory augmentation of the IGF‐I‐survival signaling and inhibition of apoptosis

Abstract: Consumption of deep sea minerals (DSM), such as magnesium, calcium, and potassium, is known to reduce hypercholesterolemia-induced myocardial hypertrophy and cardiac-apoptosis and provide protection against cardiovascular diseases. Heart diseases develop as a lethal complication among diabetic patients usually due to hyperglycemia-induced cardiac-apoptosis that causes severe cardiac-damages, heart failure, and reduced life expectancy. In this study, we investigated the potential of DSM and its related cardio-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 41 publications
3
18
0
Order By: Relevance
“…In this study, the C57/BL6 mice showed increase in the IGF‐1R survival mechanism as a compensative protective mechanism against HFD and andrographolide treatment further upregulated the IGF‐1R survival mechanism and fortified the cardio‐protection in obese mice (Figure ). Furthermore, our previous studies on obesity and diabetes in Zuker rats, SD rats, C57/BL6 mice and in hamsters showed a common set of changes in cardiac tissue morphology such as cardiac tissue disarray, increased interstitial space, and minor cardiac fibrosis, and further displayed significantly increased protein levels of Fas ligand, Fas death receptors, and FADD . In this study, HFD feeding in C57/BL6 mice triggered increase in the number of TUNEL‐positive apoptotic cells in heart and further caused minor cardiac fibrosis.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…In this study, the C57/BL6 mice showed increase in the IGF‐1R survival mechanism as a compensative protective mechanism against HFD and andrographolide treatment further upregulated the IGF‐1R survival mechanism and fortified the cardio‐protection in obese mice (Figure ). Furthermore, our previous studies on obesity and diabetes in Zuker rats, SD rats, C57/BL6 mice and in hamsters showed a common set of changes in cardiac tissue morphology such as cardiac tissue disarray, increased interstitial space, and minor cardiac fibrosis, and further displayed significantly increased protein levels of Fas ligand, Fas death receptors, and FADD . In this study, HFD feeding in C57/BL6 mice triggered increase in the number of TUNEL‐positive apoptotic cells in heart and further caused minor cardiac fibrosis.…”
Section: Discussionsupporting
confidence: 58%
“…In addition, mitochondrial‐dependent intrinsic cardiac apoptosis is also observed in obese condition . Interruption of apoptosis is understood to be one of the possible strategies to reverse or attenuate cardiac disorders and in this regard, several alternative approaches are considered for their anti‐apoptotic benefits against obesity, DM and other pathological conditions . Andrographis paniculata (Burm.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, by using high fat diet‐induced diabetic animal models, DSW has been proven to exert an antidiabetic effect and protects cardiovascular system . Our previous research demonstrates that the consumption of deep sea minerals possesses several protective effects in a streptozotocin (STZ)‐induced diabetic rat model, such as amelioration of apoptotic liver damage and a prolonged life span . However, the molecular mechanisms which underlie the benefits of DSW on diabetic cardiomyopathy are still largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…24 Our previous research demonstrates that the consumption of deep sea minerals possesses several protective effects in a streptozotocin (STZ)-induced diabetic rat model, such as amelioration of apoptotic liver damage 25 and a prolonged life span. 26 However, the molecular mechanisms which underlie the benefits of DSW on diabetic cardiomyopathy are still largely unknown. Thus, the purpose of this present study is to investigate whether DSW protects against inflammation in cardiomyocytes of STZ-induced diabetic rat.…”
Section: Introductionmentioning
confidence: 99%
“…During apoptosis induction in a cell, the cysteine protease caspase‐8 cleaves Bid to its truncated form (tBid) which eventually destabilize the mitochondria. To counteract such apoptotic initiation, it is essential to maintain the homeostatic proportions of these pro‐apoptotic and pro‐survival members of Bcl‐2 such as the protein Bcl‐2 and Bcl‐xL . In this regard, IGF1 survival signaling is seen as a compensatory mechanism to attenuate the apoptosis initiation in various cardiac conditions .…”
Section: Introductionmentioning
confidence: 99%